HIGH-TECH MEDICAL CARE TO RESTORE BLOOD FLOW IN PATIENTS WITH RESTENOSIS - Saidov M.A; Nizamov H.S; Kushnazarov R.S; Achilova Sh.S; Xamidov I.N; Ruzieva A.A (Scholar Express Journals, 2023)
The purpose of the study is to justification of the choice of a surgical method for the treatment of restenosis
Keywords: percutaneous intervention; stenting; restenosis